Expanding the Studentsâ Vocabulary by Using Language Games - Noho, Hanswaty (Proceeding of International Conference on Teacher Training and Education, 2016)
The aim of this research is to investigate whether the games techniques can improve the studentsâ vocabulary in the English learning. This research was conducted the second class of SMK Almamater Telaga by taking 30 students as a sample. The method used is quasi experimental one with research design one group of pre-test and posttest design. The data were collected from a test, notably vocabulary multiple choice test consists of 35 items. Each item has been analyzed by using item analysis in order to take its validity and reliability. The results indicate that the studentsâ vocabulary can be expanded by using the Games technique. It is proved by the result of statistical analysis in which the criteria used to verify the hypothesis of this research was received Ho if t count< t test. In this cases, t count = -2.36 and t list = 2.00.By looking the result of the data analysis, it can be concluded that the studentsâ vocabulary increase after treatment. It means that the vocabulary teaching by using games promise better result.Based on the results of the study, it is recommended that language games be implemented in teaching English, especially in other English language components and English language skills.